ANALISIS FAKTOR PENYEBAB RENDAHNYA KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS III SDN DASAN BARU INPRES: Penelitian Kualitatif deskriptif - Hikmatun Anisa; Heri Hadi Saputra; Muhammad Sobri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine students' reading abilities and the factors causing low initial reading abilities in third-grade students. The data sources used in this study were students, class teachers, and the principal. Data collection techniques were carried out using observation, documentation, and in-depth interviews. The data analysis technique used was the Interactive model from Miles & Huberman (2021), which consists of several components: data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that students' reading abilities are still relatively low because they cannot reach the initial reading ability indicators. This is caused by two factors: internal factors, namely low intellectual ability, lack of interest and motivation. External factors include the lack of parental involvement, the less than optimal role of teachers, and the lack of adequate school environmental infrastructure.